Dynamics of auger working body of a multifunctional conveyor - Hevko, B.; Lyashuk, O.; Sokil, M.; Skyba, O.; Marunych, O.; Shmatko, D. (Bulletin of the Karaganda University. Mathematics Series, 2018)
A mathematical model of bending oscillations of a multifunctional conveyor working body with consideration of the angular velocity of its rotation and the motion along its outdoor medium is developed. Based on this model, the analytical relations were defined that describe the laws of changing the defining parameters of the working body oscillations for both non - resonant and resonant cases. The amplitude of the transition through the resonance is found to depend greatly on the relative quantity of medium motion and the rate of transition through the resonance.